2006
DOI: 10.1021/jp062740l
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic C−H/π Interactions:  Methane−Benzene, Methane−Phenol, and Methane−Indole Complexes

Abstract: Noncovalent C-H/pi interactions are prevalent in biochemistry and are important in molecular recognition. In this work, we present potential energy curves for methane-benzene, methane-phenol, and methane-indole complexes as prototypes for interactions between C-H bonds and the aromatic components of phenylalanine, tyrosine, and tryptophan. Second-order perturbation theory (MP2) is used in conjunction with the aug-cc-pVDZ and aug-cc-pVTZ basis sets to determine the counterpoise-corrected interaction energy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
186
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(220 citation statements)
references
References 42 publications
33
186
0
1
Order By: Relevance
“…The RVS-SCF results in Table 6 may also be compared with analogous SAPT2 results from the literature for the methane (E elst ) -1.153, E exch ) 2.164, E disp ) -2.025 kcal/mol) 24 and hydrogen sulfide complexes (E elst ) -3.18, E exch ) 4.19, E disp ) -4.16 kcal/mol). 10 Although the SAPT2 total and component energies differ from the RVS-SCF results by up to 21%, the overall breakdown profile is similar, irrespective of the method used.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The RVS-SCF results in Table 6 may also be compared with analogous SAPT2 results from the literature for the methane (E elst ) -1.153, E exch ) 2.164, E disp ) -2.025 kcal/mol) 24 and hydrogen sulfide complexes (E elst ) -3.18, E exch ) 4.19, E disp ) -4.16 kcal/mol). 10 Although the SAPT2 total and component energies differ from the RVS-SCF results by up to 21%, the overall breakdown profile is similar, irrespective of the method used.…”
Section: Resultsmentioning
confidence: 96%
“…2,10 In particular, Grimme has recently noted that very accurate ab initio data are still missing for complexes of benzene with small molecules. 2 Therefore, the purpose of this paper is to build on previous studies of benzene-small molecule complexes [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] to provide equilibrium binding energies (D e ) and potential energy curves with "subchemical" accuracy (i.e., accurate to within a fraction of a kcal/mol) for such systems. For systems where the zero-point energy has also been accurately determined, the vibrationally averaged binding energy (D 0 ) is calculated and compared with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] These interactions play important role in crystal packing, biomolecular recognition processes, and various aspects of materials science. 1,2 Special importance has been given to benzene dimer because it can serve as a prototype for -interactions in aromatic systems.…”
Section: Department Of Chemistry Interdisciplinary Center Formentioning
confidence: 99%
“…Recently, substituent effects on -interactions in the benzene dimer have stimulated theoretical interest. [13][14][15][16] An excellent work of Wheeler and Houk 16 has revealed that additional dispersive interactions between the substituents and the other benzene ring play crucial role in stabilizing most of the substituted benzene dimers. In our group, we have investigated theand cation-interactions of large molecular systems.…”
Section: Department Of Chemistry Interdisciplinary Center Formentioning
confidence: 99%
“…The ammonia…benzene, water…benzene, HCN…benzene and T-benzene (C 2v ) dimer complexes involve a weak hydrogen bond between the hydrogen atom of the donor non-benzene molecule interacting with the delocalised π-system of the benzene ring. The stackedbenzene (C 2h ) dimer involves a π-π stacking interaction, and the methane…benzene complex involves a C-H/π bond, common in protein side chains [31].…”
Section: Introductionmentioning
confidence: 99%